2022
DOI: 10.3390/app121910133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Behavior of Vehicle Drivers at Signal-Controlled Intersection Approach while Waiting for a Green Signal—A Case Study in Poland

Abstract: The article presents the results of research on the behavior of vehicle drivers who, in the congested city road network (during the transport peak period), were unable to pass a traffic light-controlled intersection during one signaling cycle. They were therefore forced to wait in line at least once on the red signal before they could continue their journey. Empirical research was conducted at several intersections with traffic lights in Poland, in the cities of Bydgoszcz and Toruń. In addition, the database w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…In the field research results, it was observed that 60% of drivers who had stopped their vehicles after the red light came on used their mobile phones. In addition, according to the results of the survey, less than 40% of drivers admitted that they exhibited this behavior [36].…”
Section: Literature Reviewmentioning
confidence: 98%
“…In the field research results, it was observed that 60% of drivers who had stopped their vehicles after the red light came on used their mobile phones. In addition, according to the results of the survey, less than 40% of drivers admitted that they exhibited this behavior [36].…”
Section: Literature Reviewmentioning
confidence: 98%